2018
DOI: 10.1155/2018/1053815
|View full text |Cite
|
Sign up to set email alerts
|

The Association between Glucose Control and Functional Indices in Older People with Diabetes

Abstract: Diabetes may be viewed as a disease of accelerated aging as it is a risk factor for physical disability and impairment in simple and complex activities, and is a higher risk for falls and fractures. Data from the last several years suggests that this increased risk is due not only to recognized diabetes complications but also to an accelerated decline in physical capacity due to lower muscle quality and a more rapid decline in muscle mass and lower extremity strength over time. Aim. To find the association bet… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
3
1

Year Published

2021
2021
2025
2025

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 34 publications
(44 reference statements)
0
3
1
Order By: Relevance
“…It may be because the mean age in Azmon et al (2018) [ 18 ] study was much older (70.7 vs 53 [40–59] years) and the duration of T2DM was much longer (17.09 vs. 7 [0–30] years) than our study. Furthermore, the GS was measured with different method, using a 10-m walk test with an addition of 2 m for acceleration at the beginning and 2 m for deceleration at the end [ 18 ]. The mean usual GS of all subjects in our study was also still normal based on AWGS 2019 criteria (1.02 [0.23] m/s).…”
Section: Discussioncontrasting
confidence: 64%
See 3 more Smart Citations
“…It may be because the mean age in Azmon et al (2018) [ 18 ] study was much older (70.7 vs 53 [40–59] years) and the duration of T2DM was much longer (17.09 vs. 7 [0–30] years) than our study. Furthermore, the GS was measured with different method, using a 10-m walk test with an addition of 2 m for acceleration at the beginning and 2 m for deceleration at the end [ 18 ]. The mean usual GS of all subjects in our study was also still normal based on AWGS 2019 criteria (1.02 [0.23] m/s).…”
Section: Discussioncontrasting
confidence: 64%
“…Our study found no significant correlation between glycaemic control and GS. In contrast, Azmon et al (2018) [ 18 ] reported significant negative weak correlation between HbA1c and GS among T2DM elderly patients ( r = −0.208; p = 0.007). It may be because the mean age in Azmon et al (2018) [ 18 ] study was much older (70.7 vs 53 [40–59] years) and the duration of T2DM was much longer (17.09 vs. 7 [0–30] years) than our study.…”
Section: Discussionmentioning
confidence: 92%
See 2 more Smart Citations